Conceptual design and thermodynamic assessment of an integrated sCO2 Waste-Heat recovery system for sustainable co-generation of ammonia - Hamza Ahmed; Tariq Talha; Muhammad Shoaib Ahmed Khan; Usama Perwez; Abdur Rehman Mazhar; Muhammad Rehan Khan; Talha Irfan Khan (Fuel, 2027)

Polymeric Based Bioinspired Microneedle Patch for the Treatment of Androgenetic Alopecia (AGA) - Muhammad Irfan Siddique; Shaher Bano; Muhammad Sarfraz; Arslan Ghazanfar; Talha Jawaid; Tahir Ali Chohan; Muhammad Naeem; Abida Khan (Journal of Pharmaceutical Innovation, 2026)

Chitinase-primed ultrasound enhances Saccharomyces cerevisiae cell-wall deconstruction and yeast-protein remodelling in two complementary model systems - Talha Riaz; Xianjiang Ye; Te Yu; Zhijun Xia; Muhammad Moeid Khan; Xuan Yao; Rabiya Riaz; Sadia Ansar; Zhou Chen; Muhammad Atiq Ashraf; Chuanyan Pan; Yongguo Jin; et al. (Food Research International, 2026)

Watershed-agnostic modeling: An explainable, distributed, data-driven hydrologic model - Muhammad Talha; A. Pouyan Nejadhashemi (Environmental Modelling & Software, 2026)

Lornoxicam Loaded Transethosomal Gel: Formulation, Box-Behnken Optimization, Ex-Vivo and In-Vivo Characterization - Minahal Munir; Sarah Ahmad; Talha Jamshaid; Huma Hameed; Muhammad Zaman; Usama Jamshaid; Muhammad Jamshaid; Sara Khalid; Heba A. Gad (Journal of Pharmaceutical Innovation, 2026)

Optogenetic Pacemaker Cells for Biological Cardiac Rhythm Management in Sick Sinus Syndrome - Versha Devi; Syeda Aliza Aamir; Syed Abdullah Shah; Muhammad Dawood Ghaffar; Muhammad Talha; Muneeb Saifullah (Cell Biochemistry and Biophysics, 2026)

CRISPR-Cas systems for enhancing chilling tolerance in rice: recent advances and future prospects - Muhammad Sikandar Zaman; Asad Azeem; Ayesha Nouman; Abdullah Khalid; Saira Ghafoor; Muhammad Zia Ul Haq; Muhammad Talha Aslam; Hossam S. El-Beltagi (Biologia Futura, 2026)

Faster-developing buffalo embryos produced in vitro demonstrate higher quality, enhanced pregnancy rates, and distinct transcriptome profile - Muhammad Waqas; Qaisar Shahzad; Armughan Ahmad Wadood; Talha Ashraf; Ali Husnain; Muhammad Khurram Shahzad; Huiyan Xu; Liping Pu; Yangqing Lu (Theriogenology, 2026)

Botulinum toxin from foodborne hazard to aesthetic and biomedical tool: mechanisms, applications, detection strategies, and future perspectives - Muhammad Adnan; Muhammad Waqar; Rais Ahmed; Haroon Afzal; Muhammad Abdullah Mueen; Urooj Qayyum; Farhang Hameed Awlqadr; Muhammad Talha Yaqoob; Sabrin R. M. Ibrahim; Gamal A. Mohamed; Iqra Rafiq; Hagar M. Mohamed (Archives of Microbiology, 2026)

Protective effects of zinc and Prunus amygdalus against cadmium-induced nephrotoxicity in male Albino rats - Muhammad Talha Ishaq; Faiza Zubair; Naila Riaz; Hira Kanwal; Ayesha Tehreem Shahbaz; Tooba Tahir; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Journal of Trace Elements in Medicine and Biology, 2026)

Synergistic effects of pulsed electric field and ultrasound on microstructure and bioactive properties of fresh and old ginger juice - Zhong Han; Wenhao Xiao; Ji Ma; Muhammad Mohsin Raza; Xin-An Zeng; Muhammad Faisal Manzoor; Muhammad Talha Afraz (Journal of Food Engineering, 2026)

Unlocking the Hydrocarbon Potential of the Canterbury Basin, New Zealand: Geochemical and Basin Modeling Insights for Hydrocarbon Exploration - Muhammad Ubaid Umar; Shenghe Wu; S. M. Talha Qadri; Shafqat Hussain; Khaled Albriki; Muhammad Riaz (Natural Resources Research, 2026)

Chemical Profile, Biological Activities, Molecular Docking, and Density Functional Theory (DFT) of Cymbopogon citratus Essential Oil Extracted By Conventional and Superheated Steam Extraction Techniques - Muhammad Adnan Ayub; Fiza Bashir; Khayala Mammadova; Muhammad Talha Anjam; Muhammad Ijaz; Amjad Hussain; Mohamed Fawzy Ramadan; Fahim Arshad; Muhammad Zubair (Journal of Pharmaceutical Innovation, 2026)

Comparative evaluation of carbon sequestration and climate change mitigation in commercially planted eucalyptus-based agroforestry systems in a semi-arid region - Ghulam Yasin; Muhammad Azeem Akhter; Muhammad Zubair; Muhammad Talha Imtiaz; Matoor Mohsin Gilani; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Dilnoza Sotiboldiyeva; Shafeeq Ur Rahman (Journal of Environmental Studies and Sciences, 2026)

Appropriate selection of objective functions with constraints for successive multicycle optimization of the HPR1000 reactor core using deep learning enhanced multi-objective genetic algorithm - Muhammad Kamran Butt; Samia Nasir; Muhammad Ahmad; Muhammad Talha Bin Humayun; Ahmer Riaz; Chenghui Wan; Liangzhi Cao (Annals of Nuclear Energy, 2026)

Leveraging Extremophyte Adaptations as a Roadmap for Crop Design for Arid Lands - Mohsin Tanveer; Lei Wang; Hamza Tariq; Muhammad Talha Ramzan; Alisdair R. Fernie; Jaume Flexas; Sergey Shabala; Josep Peñuelas (Global Change Biology, 2026)
Anthropogenic climate change is driving a convergence of rapid soil aridification and secondary salinization that threatens to degrade over half of the world's arable land. As conventional glycophytic crops reach their physiological limits, global food security depends on decoding the evolutionary adaptations of extremophytes. This review synthesizes the functional traits and ecosystem‐level impacts of extremophytes, the native flora of these marginal environments, and evaluates their potential as a biophysical buffer against land degradation. Here, we identify two cornerstone strategies that allow these plants to thrive where others fail: (i) the precise spatiotemporal orchestration of reactive oxygen species (ROS) as critical signaling molecules for developmental plasticity; and (ii) the active recruitment of stress‐protective microbiomes via targeted exudation, effectively transforming barren soil into a functional ecosystem. We argue that integrating extremophytes into diversified agroecosystems, through intercropping, phytoremediation rotations, and circular bioeconomy models, offers quantifiable results to enhance ecosystem multifunctionality and sustainably intensify production on degrading lands. By bridging profound mechanistic discovery with ecological engineering, this perspective provides an actionable plan for translating extremophyte biology into crops capable of withstanding a drier future.

Processing sequence as a design lever: pectin pre-complexation enhances ultrasound-driven interfacial loading, functionality, and volatile profile of yeast protein - Talha Riaz; Yuan Ma; Zhijun Xia; Muhammad Moeid Khan; Xianjiang Ye; Muhammad Atiq Ashraf; Rabiya Riaz; Xing Fu; Yongguo Jin (Food Research International, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Atraric acid mitigates the cognitive and pathological deficits in mice via Aβ1−42 induced Alzheimer’s disease - Waqar Ali; Kyonghwan Choe; Talha Nasir; Uzair Atiq; Muhammad Tahir; Waqas Ahmad; Hyun Young Park; Tae Ju Park; Myeong Ok Kim (Inflammopharmacology, 2026)

Performance of ambient cured fly ash-slag based geopolymer concrete reinforced with glass wool and nylon fibres - Hussnain Haider; Shehroze Ali; Muhammad Talha Ghafoor (Innovative Infrastructure Solutions, 2026)

Trends in ADR reporting’ and the missing context: COVID-19, LMICs, and sociodemographic blind spots - Talha Ali; Muhammad Salman; Mateen Khan (European Journal of Clinical Pharmacology, 2026)

Species-specific snag use and nesting ecology of cavity-nesting birds in managed plantations of Southern Punjab, Pakistan - Muhammad Talha Imtiaz; Ihsan Qadir; Kathryn E. Sieving; Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Zubair (Environmental Monitoring and Assessment, 2026)

Coated Urea Improves Productivity and Nitrogen Use Efficiency in Wheat - Muhammad Talha Aslam; Imran Khan; Muhammad Umer Chattha; Ghulam Murtaza (Journal of Soil Science and Plant Nutrition, 2026)

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Precision Rewiring of Stress-Responsive Gene Networks Via CRISPR: Mechanistic Pathways Toward Climate-Smart Agriculture - Burhan Khalid; Muhammad Umer Javed; Muhammad Ikram; Muhammad Ateeq; Muhammad Atiq Ashraf; Talha Riaz; Shumaila Nawaz; Rizwan Maqbool (Journal of Crop Health, 2026)

Virophages: mechanisms, ecological Roles, and therapeutic potential in combating giant virus infections - Muhammad Talha; Mehak Faisal; Amna Mujtaba; Amna Amjad; Nouraiz Abbas; Laiba Shamim; Fakhar e Mahin; Muammar Hassan; Muhammad Daim Hassan; Muhammad Abdur Rehman Awaisi (Archives of Microbiology, 2026)

Short dry period improves postpartum energy balance and reproduction but reduces milk yield in dairy cows - Melad Ahmed; Amjad Riaz; Nasim Ahmad; Muhammad Naveed ul Haque; Hifz ul Rahman; Muhammad Yaseen; Talha Ashraf; Muhammad Abdullah; Ali Hassan; Ali Husnain (Theriogenology, 2026)

Reimagining human creativity and learning in the age of generative AI: A multi-method meta-thematic synthesis - Muhammad Bilal Zafar; Hassnian Ali; Talha Yasin (Next Research, 2025)

Next-generation wearable ECG systems: Soft materials, AI integration, and personalized healthcare applications - Bangul Khan; Rana Talha Khalid; Muhammad Hasan Masrur; Muhammad Awais; Bilawal Khan; Bee Luan Khoo (Chemical Engineering Journal, 2025)

Understanding the role of Hedgehog signaling pathway and gut dysbiosis in fueling liver cancer - Naz Fatima; Hooriya Fatima; Sadia Ahmad; Muhammad Abu Talha Safdar Hashmi; Nadeem Sheikh (Molecular Biology Reports, 2025)

Machine learning-driven porosity prediction: A case study from the Cretaceous Mata Series, Canterbury Basin, New Zealand - Muhammad Ubaid Umar; Shenghe Wu; S.M. Talha Qadri; Wakeel Hussain; Du Wei; Shaukat Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Bridging the resolution gap: Machine learning for local-scale groundwater drought monitoring in Punjab, Pakistan - Fahimeh Youssefi; Shoaib Ali; Behnam Khorrami; Mohammad Mohsin Khan; Muhammad Jehanzaib; Talha Mahmood; Zhiming Han; Wu Haotian; Muhammad Faisal (Groundwater for Sustainable Development, 2025)

Airborne particulate matter reduction through developed dust control systems for wheat thresher - Talha Mehmood; Zia- Ul-Haq; Tahir Iqbal; Muhammad Ansar (Air Quality, Atmosphere & Health, 2025)

Offshore wind resource assessment and 7E analysis of offshore wind farms on the coastal belt of Pakistan - Talha Bin Nadeem; Asad A. Naqvi; Muhammad Saad; Kinza Malik; Ahsan Ahmed (Process Safety and Environmental Protection, 2025)

Stem cell therapy: a promising frontier in modern medicine with a comprehensive overview of their biology and potential therapeutic applications in chronic non-healing cutaneous injuries - Qadeer Ahmad; Shumaila Mehdi; Malik Hassan Mehmood; Muhammad Talha Asif; Muhammad Mohsin Ali (Inflammopharmacology, 2025)

Evaluation of testicular protective effects of Prunus amygdalus and zinc against cadmium induced toxicity in rats - Ayesha Tehreem Shahbaz; Faiza Zubair; Naila Riaz; Hira Kanwal; Tooba Tahir; Muhammad Talha Ishaq; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Environmental Science and Pollution Research, 2025)

Effect of Bioactive Peptides and Encapsulated Butyric Acid on Growth Performance, Gut Health, Immune Status and Nutrient Digestibility in Broiler Chickens - Mohammad Ahmad Qazi; Ehsaan Ullah Khan; Saima Naveed; Shahid Mehmood; Muhammad Muneeb; Muhammad Talha; Muhammad Shabir Shaheen; Sohail Ahmad (International Journal of Peptide Research and Therapeutics, 2025)

Development of empirical models for forecasting of global solar radiations for different climatic regions of Pakistan - Talha Bin Nadeem; Yousuf Baig; Muhammad Talha Ansari (Next Research, 2025)

Predicting ground-level PM 2.5 using high-resolution satellite imagery and machine learning algorithms with ground-based validation - Muhammad Hamza Tariq; Musawar Hussain; Muhammad Mahad Khaliq; Talha Saeed; Michael Howard Bergin; Muhammad Fahim Khokhar (International Journal of Remote Sensing, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

Influence of Aloe Vera Gel and Neem Extract Application on Postharvest Quality and Shelf Life of Prunus persica - Muhammad Talha; Moazzam Anees; Mubeen Sarwar; M. Rizwan Tariq; Zain Mushtaq; Abdulrahman Alasmari; Anum Nazir; Nazir Ahmad (Applied Fruit Science, 2025)

A framework for addressing water–rock interaction (WRI) for sustainable water resources development using various simulation models: Review - Naseem Akhtar; Abdassalam A. Azamzam; Saleh Ali Tweib; Hamza Mohamed Flafel; Dani Wijaya; Leila Bouida; Pahmi Husain; Shahwaz Khan; Mohd Talha Anees; Muhammad Irman Khalif Ahmad Aminuddin; Shubham Sharma; Rajesh Singh; et al. (Environment, Development and Sustainability, 2025)

Adaptive responses of trees to industrial pollution: modulation of leaf anatomical, physio-biochemical, and heavy metal accumulation traits in urban biotopes - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Mansoor Javaid; Usman Zulfiqar; Nafosat Djonibekova; Anarjan Matkarimova; Hesham S. Almoallim; Mohammad Javed; Shafeeq Ur Rahman (Environmental Monitoring and Assessment, 2025)

Identification of the blue-sky conditions in Punjab, Pakistan by exploiting satellite and ground-based observations, and policy implications - Hira Saif; Talha Saeed; Musawar Hussain; Afnan Ullah; Muhammad Fahim Khokhar (International Journal of Remote Sensing, 2025)

Experimental study of unglazed transpired solar collectors integrated with buildings in humid sub-tropics - Tariq Talha; Muhammad Talha; Shuli Liu; Abdur Rehman Mazhar; Usama Perwez; Muhammad Moiz; Ahtasham Afzal (Energy and Buildings, 2025)

Plant Growth Promoting Rhizobacteria Regulated Nutrient Uptake in Quinoa (Chenopodium Quinoa Wild) Under Nutrient-Deficient Conditions Through Solubilizing Insoluble Minerals - Ejaz Rafique; Muhammad Zahid Mumtaz; Lingling Li; Inam Ullah; Talha Ali Chohan; Muhammad Waqar Alam; Adnan Mustafa; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Novel approaches to reduce airborne pathogen infestation through dust control systems of wheat thresher - Talha Mehmood; Zia-Ul-Haq; Tahir Iqbal; Muhammad Ansar (Aerobiologia, 2025)

Selecting Relevant Features for Random Forest-Based Crop Type Classifications by Spatial Assessments of Backward Feature Reduction - Talha Mahmood; Muhammad Usman; Christopher Conrad (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)
Random Forest (RF) is a widely used machine learning algorithm for crop type mapping. RF’s variable importance aids in dimension reduction and identifying relevant multisource hyperspectral data. In this study, we examined spatial effects in a sequential backward feature elimination setting using RF variable importance in the example of a large-scale irrigation system in Punjab, Pakistan. We generated a reference classification with RF applied to 122 SAR and optical features from time series data of Sentinel‑1 and Sentinel‑2, respectively. We ranked features based on variable importance and iteratively repeated the classification by excluding the least important feature, assessing its agreement with the reference classification. McNemar’s test identified the critical point where feature reduction significantly affected the RF model’s predictions. Additionally, spatial assessment metrics were monitored at the pixel level, including spatial confidence (number of classifications agreeing with the reference map) and spatial instability (number of classes occurring during feature reduction). This process was repeated 10 times with ten distinct stratified random sampling splits, which showed similar variable rankings and critical points. In particular, VH SAR data was selected when cloud-free optical observations were unavailable. Omitting 80% of the features resulted in an insignificant loss of only 2% overall accuracy, while spatial confidence decreased by 5%. Moreover, the crop map at the critical point exhibited an increase in spatial instability from a single crop to 1.28. McNemar’s test and the spatial assessment metrics are recommended for optimized feature reduction benchmarks and identifying areas requiring additional ground data to improve the results.

Optimisation led energy-efficient arsenite and arsenate adsorption on various materials with machine learning - Jinsheng Huang; Waqar Muhammad Ashraf; Talha Ansar; Muhammad Mujtaba Abbas; Mehdi Tlija; Yingying Tang; Yunxue Guo; Wei Zhang (Water Research, 2025)

Effect of human chorionic gonadotropin on oocyte maturation and developmental competence in buffalo - Muhammad Bilal; Muhammad Kamran Ashraf; Talha Ashraf; Muhammad Yaseen; Ali Husnain; Muhammad Bilal Bin Majeed; Muhammad Imran; Burhan E. Azam Rana; Muhammad Hassan Mushtaq; Amjad Riaz (Theriogenology, 2025)

Research on optimal design of multi-energy microgrid considering hybrid resilience load management and Carbon emissions - Talha Rehman; Muhammad Ahsan Khan; Hak-Man Kim (Sustainable Cities and Society, 2025)

Reshaping the healthcare world by AI-integrated wearable sensors following COVID-19 - Bangul Khan; Rana Talha Khalid; Khair Ul Wara; Muhammad Hasan Masrur; Samiullah Khan; Wasim Ullah Khan; Umay Amara; Saad Abdullah (Chemical Engineering Journal, 2025)

Overview of industrial food fraud and authentication through chromatography technique and its impact on public health - Nabila Aslam; Rida Fatima; Ammar B. Altemimi; Talha Ahmad; Samran Khalid; Syed Ali Hassan; Rana Muhammad Aadil (Food Chemistry, 2024)

Utilizing Cinnamomum verum (a culinary spice), as a functional food ingredient ameliorating hypercholesterolemia: In-vivo, in-vitro, and in-silico multi-model analysis - Mahnoor Bano; Muhammad Khurram Waqas; Talha Ali Chohan; Fakhra Batool; Aamir Mushtaq; Yahya I. Asiri; Mohd. Zaheen Hassan; Md Ali Mujtaba; Md. Khalid Anwer; Muhammad Irfan Sidique; Ayesha Riaz; Umair Khurshid; et al. (Food Bioscience, 2024)

Identification of novel antimicrobial compounds in colostrum-associated Lactiplantibacillus plantarum ZFS 1 and 2 by integrating in vitro, machine learning and bioinformatics approaches - Zainab Fiaz; Fatima Noor; Aqsa Ikram; Talha Ali Chohan; Muhammad Zubair Aslam; Najma Arshad (Food Bioscience, 2024)

Advancements in sustainable production of biofuel by microalgae: Recent insights and future directions - Muhammad Abdullah; Zain Ali; Muhammad Talha Yasin; Kinza Amanat; Fatima Sarwar; Jallat Khan; Khurshid Ahmad (Environmental Research, 2024)

Efficacy and safety of ticagrelor monotherapy following a brief DAPT vs. prolonged 12-month DAPT in ACS patients post-PCI: a meta-analysis of RCTs - Usama Qamar; Farhan Naeem; Muhammad Talha Maqsood; Maleeka Zamurad Khan; Zeeshan Imtiaz; Fatima Saeed; Neelesh Gupta; Fnu Zafarullah Brohi; Celestine Mkpozi; Yasar Sattar (European Journal of Clinical Pharmacology, 2024)

Evaluating machine learning approaches for aboveground biomass prediction in fragmented high-elevated forests using multi-sensor satellite data - Asim Qadeer; Muhammad Shakir; Li Wang; Syed Muhammad Talha (Remote Sensing Applications: Society and Environment, 2024)

Comprehensive assessment of heavy metal contamination in soil-plant systems and health risks from wastewater-irrigated vegetables - Muhammad Anis Aslam; Muhammad Sohail Abbas; Muhammad Mustaqeem; Maryam Bashir; Adeeba Shabbir; Muhammad Talha Saeed; Rana Muhammad Irfan (Colloids and Surfaces C: Environmental Aspects, 2024)

Valorization of poultry slaughter wastes via extraction of three structural proteins (gelatin, collagen and keratin): A sustainable approach for circular economy - Muhammad Talha; Muhammad Tanveer; Aqsa Abid; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Hira Shair; Nimra Tanveer; Almas Mustafa (Trends in Food Science & Technology, 2024)

Bovine colostrum: Therapeutic potential and clinical evidence - Talha Shireen Khan; Noor Akram; Zargham Faisal; Farhan Saeed; Amara Rasheed; Faiyaz Ahmed; Muhammad Afzaal (International Dairy Journal, 2024)

Effect of supplementing epinephrine in maturation media on in-vitro developmental competence of cattle and buffalo oocytes - Abdul Khaliq; Muhammad Ameer Hamza; Talha Ashraf; Ali Husnain; Muhammad Yaseen; Abdul Rehman; Muhammad Binyameen; Muhammad Yasir Zahoor; Amjad Riaz (Theriogenology, 2024)

Punching shear strength of fiber-reinforced polymer concrete slabs: Database-driven assessment of parameters and prediction models - Aroob Alateyat; Raghad Awad; Basil Ibrahim; Muhammad-Talha Junaid; Salah Altoubat; Mohamed Maalej; Samer Barakat (Engineering Structures, 2024)

Potato Chip Varietal Analysis: a Comparative Evaluation Based on Potato Cultivars - Talha Khalil; Muhammad Haroon; Sumaira Miskeen; Shehla Sammi; Muhammad Jahangir; Sara Najeeb; Kainat Nisar; Arsalan Khan; Muhammad Liaquat; Imran Khan; Jae-Won Ha (Potato Research, 2024)

The limits to equity in water allocation under scarcity - Wasim Hassan; Talha Manzoor; Abubakr Muhammad (Journal of Hydrology, 2024)

Synergistic effect of biochar with gypsum, lime, and farm manure on the growth and tolerance in rice plants under different salt-affected soils - Yousef Alhaj Hamoud; Talha Saleem; Muhammad Zia-ur-Rehman; Hiba Shaghaleh; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Faisal Al-Sarraj; Nadiyah M. Alabdallah (Chemosphere, 2024)

Design and optimization of off-grid solar PV and biomass-based hybrid renewable energy system (HRES) for electrification of a rural community in Tharparkar, Pakistan - Talha Bin Nadeem; Ahsan Ahmed; Muhammad Saad; Asad A. Naqvi (Environment, Development and Sustainability, 2024)

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

Toxicological profile and potential health concerns through metals and trace elements exposure in brick kiln workers from Lahore, Pakistan - Talha Saeed; Naeem Akhtar Abbasi; Muhammad Talha Zahid; Noor Fatima; Kaleem Ullah; Muhammad Fahim Khokhar (Environmental Geochemistry and Health, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Remimazolam versus propofol for sedation in gastrointestinal endoscopy and colonoscopy within elderly patients: a meta-analysis of randomized controlled trials - Wania Ahmer; Sahar Imtiaz; Daniyal Muhammad Alam; Khadija Ahmed; Barka Sajid; Juvairia Yousuf; Sunny Asnani; Muhammad Ahmed Ali Fahim; Rahmeen Ali; Marium Mansoor; Muhammad Talha Safdar; Muhammad Umair Anjum; et al. (European Journal of Clinical Pharmacology, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

Pathways to ecological resilience: exploring green energy and finance for sustainable development - Iqra Mehroush; Wasim Abbas Shaheen; Mohsin Shabir; Muhammad Talha (Environment, Development and Sustainability, 2024)

Organic waste-to-bioplastics: Conversion with eco-friendly technologies and approaches for sustainable environment - Zain Ali; Muhammad Abdullah; Muhammad Talha Yasin; Kinza Amanat; Khurshid Ahmad; Ishfaq Ahmed; Muther Mansoor Qaisrani; Jallat Khan (Environmental Research, 2024)

Ultrasonic humidifier-assisted thermal desalination: A comprehensive review - Muhammad Talha; Awad B.S. Alquaity (Desalination, 2024)

Sustainable electric discharge machining using alumina-mixed deionized water as dielectric: Process modelling by artificial neural networks underpinning net-zero from industry - Muhammad Sana; Muhammad Asad; Muhammad Umar Farooq; Saqib Anwar; Muhammad Talha (Journal of Cleaner Production, 2024)

From biodiversity hotspot to conservation hotspot: assessing distribution, population structure, associated flora and habitat geography of threatened Himalayan Yew in temperate forest ecosystems of Kashmir - Hamayun Shaheen; Arbaz Attique; Malik Talha Riaz; Muhammad Manzoor; Raja Waqar Ahmed Khan; Muhammad Tayyib Riaz (Biodiversity and Conservation, 2024)

Deciphering the Role of Phytohormones and Osmolytes in Plant Tolerance Against Salt Stress: Implications, Possible Cross-Talk, and Prospects - Sadam Hussain; Muhammad Bilal Hafeez; Rabia Azam; Kashf Mehmood; Marjan Aziz; Sezai Ercisli; Talha Javed; Ali Raza; Noreen Zahra; Saddam Hussain; Xiaolong Ren (Journal of Plant Growth Regulation, 2024)

Bacterial inoculation remediates heavy metals toxicity through modulating biochemicals and antioxidant enzymes of Daucus carota L. grown in lead contaminated soil - Naima Huma Naveed; Naveed Abbas Nasir; Anis Ali Shah; Tahir Shahzad; Nasim Ahmad Yasin; Zain Ali; Muhammad Jamil; Talha Javed; Aamir Ali (South African Journal of Botany, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Performance and emissions characteristics of tire pyrolysis oil in diesel engine: an experimental investigation - Haseeb Yaqoob; Hafiz Muhammad Ali; Haider Abbas; Osama Abid; Muhammad Ahmad Jamil; Talha Ahmed (Clean Technologies and Environmental Policy, 2023)

Modelling of f o F 2 using artificial neural network over Equatorial Ionization Anomaly (EIA) region stations - Muhammad Ayyaz Ameen; Afnan Tahir; Madeeha Talha; Haqqa Khursheed; Imran A. Siddiqui; Syed Tanweer Iqbal; Bushra Gul (Advances in Space Research, 2023)

Co-occurrence of mycotoxins and other fungal metabolites in total mixed rations of cows from dairy farms in Punjab, Pakistan - Felipe Penagos-Tabares; Mubarik Mahmood; Muhammad Zafar Ullah Khan; Hafiz Muhammad Amjad Talha; Muhammad Sajid; Kanwal Rafique; Saima Naveed; Johannes Faas; Juan Ignacio Artavia; Michael Sulyok; Anneliese Müller; Rudolf Krska; et al. (Mycotoxin Research, 2023)
After India and the USA, Pakistan is the third country leading in global dairy production, a sector of very high socioeconomic relevance in Asia. Mycotoxins can affect animal health, reproduction and productivity. This study analysed a broad range of co-occurring mycotoxins and fungal secondary metabolites derived from Alternaria , Aspergillus , Fusarium , Penicillium and other fungal species. To complete this, a validated multi-metabolite liquid chromatography/electrospray ionization-tandem mass spectrometric (LC/ESI–MS/MS) method was employed, detecting 96 of > 500 tested secondary fungal metabolites. This first preliminary study demonstrated that total mixed rations (TMRs) ( n = 30) from big commercial dairy cattle farms (> 200 lactating cows) in Punjab, Pakistan, presented ubiquitous contamination with mixtures of mycotoxins. The mean of mycotoxins per sample was 14, ranging from 11 to 20 mycotoxins among all TMR samples. Metabolites derived from other fungi and Fusarium spp. showed the highest levels, frequency and diversity among the detected fungal compounds. Among the most prevalent mycotoxins were Fusarium toxins like fumonisins B1 (FB1) (93%), B2 (FB2) (100%) and B3 (FB3) (77%) and others. Aflatoxin B1 (AFB1) was evidenced in 40% of the samples, and 7% exceeded the EU maximum limit for feeding dairy cattle (5 µg/kg at 88% dry matter). No other mycotoxin exceeds the EU guidance values (GVs). Additionally, we found that dietary ingredients like corn grain, soybean meal and canola meal were related to increased contamination of some mycotoxins (like FB1, FB2 and FB3) in TMR from the province of Punjab, Pakistan. Among typical forage sources, the content of maize silage was ubiquitous. Individually, the detected mycotoxins represented relatively low levels. However, under a realistic scenario, long-term exposure to multiple mycotoxins and other fungal secondary metabolites can exert unpredictable effects on animal health, reproduction and productivity. Except for ergot alkaloids (73%), all the groups of metabolites (i.e. derived from Alternaria spp., Aspergillus spp., Fusarium spp., Penicillium spp. and other fungi) occurred in 100% of the TMR samples. At individual levels, no other mycotoxins than AFB1 represented a considerable risk; however, the high levels of co-occurrence with several mycotoxins/metabolites suggest that long-term exposure should be considered because of their potential toxicological interactions (additive or synergistic effects).

Glutathione and zinc application upregulate the antioxidant system increasing photosynthetic pigments and growth under water stress in maize (Zea mays L.) - Farah Saeed; Abida Kausar; Qasim Ali; Athar Mahmood; Talha Javed; Rubab Shabbir; Muhammad Fraz Ali (Brazilian Journal of Botany, 2023)

First report of Geotrichum candidum causing rose blight disease in Pakistan - Muhammad Talha Ikram; Muhammad Naveed Aslam; Anam Moosa; Faisal Zulfiqar; Muhammad Taimoor Shakeel; Roshaan Ahmed; Muneeb Anwer; Atta ur Rehman Khan (Journal of Plant Pathology, 2023)

Differential accumulation pattern of cadmium in plant parts of pea varieties in response to varying cadmium levels - Khurram Ziaf; Hafiz Muhammad Talha; Muhammad Awais Ghani; Iftikhar Ahmad; Raheel Anwar; Basharat Ali; Yasir Majeed; Amir Shakeel; Mudassar Iqbal; Abbu Zaid (South African Journal of Botany, 2023)

Experimental investigation of a solar PCM heat exchanger for indoor temperature stabilization - Aurang Zaib; Abdur Rehman Mazhar; Tariq Talha; Muhammad Inshal (Energy and Buildings, 2023)

Semi-quantitative landslide risk assessment of district Muzaffarabad, northwestern Himalayas, Pakistan - Muhammad Tayyib Riaz; Muhammad Basharat; Maria Teresa Brunetti; Malik Talha Riaz (Stochastic Environmental Research and Risk Assessment, 2023)

Correction: Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efciency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

ADU-Net: Semantic segmentation of satellite imagery for land cover classification - Muhammad Talha; Farrukh A. Bhatti; Sajid Ghuffar; Hamza Zafar (Advances in Space Research, 2023)

Enhancement in anaerobic biogas conversion by visible light photocatalytic Pre-treatment of rice husk with indium vanadate decorated titanium dioxide nanocomposite - Jamshaid Rashid; Talha Tufail Bhatti; Muhammad Hassan; M.A. Barakat; Rajeev Kumar; Ming Xu (Fuel, 2023)

Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efficiency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

Screening and growth assessment of indigenous and exotic sesame genotypes under osmotic stress - Jahangir Ahmed; Ghulam Qadir; Muhammad Fraz Ali; Talha Javed; Hafiz Muhammad Jhanzab; Fahad Masoud Wattoo; Imran Mahmood; Muhammad Ansar; Muhammad Akram Khan; Usman Zulfiqar; Bilal Ahamad Paray (South African Journal of Botany, 2023)

Variation of ionosonde f o E and its comparison with IRI-2016 & a local model over Pakistan longitude sector during solar cycle 22 - Muhammad Ayyaz Ameen; Aisha Ghulam Muhammad; Faizan Abbas; Afnan Tahir; Madeeha Talha (Advances in Space Research, 2023)

Ameliorative capacity of salicylic acid and nutrients (Ca, P, and Mg) against aluminum toxicity in sensitive pea (Pisum sativum L.) - Mohd Talha Ansari; Md Ramjan; Vivek Yadav; Majhrool Hak Ansari; Muhammad Fraz Ali (Arabian Journal of Geosciences, 2023)

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Correction to: Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

A Comprehensive Review About Bioactive Peptides: Sources to Future Perspective - Muhammad Naeem; Muhammad Inamullah Malik; Talha Umar; Swaiba Ashraf; Adnan Ahmad (International Journal of Peptide Research and Therapeutics, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Hydrogen peroxide priming alleviates salinity induced toxic effect in maize by improving antioxidant defense system, ionic homeostasis, photosynthetic efficiency and hormonal crosstalk - Muhammad Umer Chattha; Muhammad Uzair Ul Hassan; Imran Khan; Muhammad Nawaz; Adnan Noor Shah; Abdul Sattar; Mohamed Hashem; Saad Alamri; Muhammad Talha Aslam; Haifa A. S. Alhaithloul; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

Single nucleotide polymorphism based assessment of genetic diversity in local and exotic onion genotypes - Najma Tabussam; Rashid Mehmood Rana; Fahad Masoud Wattoo; Azeem Iqbal Khan; Rai Muhammad Amir; Talha Javed; Sunny Ahmar; Eldessoky S. Dessoky; Nader R. Abdelsalam (Molecular Biology Reports, 2022)

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

Comprehensive review on naringenin and naringin polyphenols as a potent anticancer agent - Abdur Rauf; Mohammad Ali Shariati; Muhammad Imran; Kashif Bashir; Shahid Ali Khan; Saikat Mitra; Talha Bin Emran; Kamala Badalova; Md. Sahab Uddin; Mohammad S. Mubarak; Abdullah S. M. Aljohani; Fahad A. Alhumaydhi; et al. (Environmental Science and Pollution Research, 2022)

An alternative approach to estimate river cross-sections using LIDAR-based digital elevation model - Mohd Talha Anees; Ahmad Farid Bin Abu Bakar; Mohammad Muqtada Ali Khan; Muhammad I. Syakir; K. Abdullah; Mohd Nawawi Mohd Nordin; Kamal Abdelrahman; Ahmed M. Eldosouky; Peter Andráš; Nasehir Khan Bin E.M. Yahaya; Zubaidi Johar; Fatehah Mohd Omar; et al. (Hydrological Sciences Journal, 2022)

Silver nanoparticles biosynthesized from secondary metabolite producing marine actinobacteria and evaluation of their biomedical potential - Ashia Alam; Faouzia Tanveer; Ali Talha Khalil; Tanzeel Zohra; Saleh Khamlich; Muhammad Masroor Alam; Muhammad Salman; Muhammad Ali; Aamer Ikram; Zabta Khan Shinwari; Malik Maaza (Antonie van Leeuwenhoek, 2021)

Correction to: Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

P53-mediated in vitro inhibition of PhIP-induced oxidative damage by myricetin bulk and nano forms in healthy lymphocytes - Shabana Akhtar; Diana Anderson; Talha Muhammad Azam; Arif Malik (Archives of Toxicology, 2021)

Alkaline lipase production by novel meso-tolerant psychrophilic Exiguobacterium sp. strain (AMBL-20) isolated from glacier of northeastern Pakistan - Muhammad Talha Yasin; Yasir Ali; Khurshid Ahmad; Abdul Ghani; Kinza Amanat; Muhammad Mudassir Basheir; Muhammad Faheem; Saddam Hussain; Bashir Ahmad; Adil Hussain; Syed Ali Imran Bokhari (Archives of Microbiology, 2021)

Heat stress in cultivated plants: nature, impact, mechanisms, and mitigation strategies—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Lorenzo Barbanti; Muhammad Aamer; Muhammad Mehmood Iqbal; Muhammad Nawaz; Athar Mahmood; Abid Ali; Muhammad Talha Aslam (Plant Biosystems, 2021)

Biochar and leguminous cover crops as an alternative to summer fallowing for soil organic carbon and nutrient management in the wheat-maize-wheat cropping system under semiarid climate - Muhammad Arif; Ikramullah; Talha Jan; Muhammad Riaz; Kashif Akhtar; Salman Ali; Shahen Shah; Fazal Jalal; Ishaq A. Mian; Khadim Muhammad Dawar; Haiyan Wang (Journal of Soils and Sediments, 2021)

Correction to: Effect of Endoxylanase and Iron Oxide Nanoparticles on Performance and Histopathological Features in Broilers - Hamza Rehman; Muzamal Akram; Mubin Mustafa Kiyani; Muhammad Talha Yasin; Abdul Ghani; Javed Iqbal Saggu; Syed Sajid Hussain Shah; Zafar Mahmood Khalid; Syed Ali Imran Bokhari (Biological Trace Element Research, 2021)

Type 1 Fimbriae and Motility Play a Pivotal Role During Interactions of Salmonella typhimurium with Acanthamoeba castellanii (T4 Genotype) - Talha Mannan; Muhammad Wasim Rafique; Muhammad Haroon Bhatti; Abdul Matin; Irfan Ahmad (Current Microbiology, 2020)

Leea macrophylla (Roxb.) root extract reverses CCl4 induced liver injury through upregulation of antioxidative gene expression: a molecular interaction for therapeutic inception - Md. Rakibul Hassan Bulbul; Md. Atiar Rahman; Md. Zillur Rahman; Talha Bin Emran; Mirola Afroze; Mala Khan; Muhammad Abid Hasan Chowdhury; Mohammed Auwal Ibrahim; Mohammed Sohel Chowdhury (Advances in Traditional Medicine, 2020)

Ecophysiological response of early stage Albizia lebbeck to cadmium toxicity and biochar addition - Muhammad Talha Bin Yousaf; Muhammad Farrakh Nawaz; Hammad Fayyaz Khawaja; Sadaf Gul; Shafaqat Ali; Irfan Ahmad; Fahd Rasul; Muhammad Rizwan (Arabian Journal of Geosciences, 2019)

Extraction optimization, total phenolic, flavonoid contents, HPLC-DAD analysis and diverse pharmacological evaluations of Dysphania ambrosioides (L.) Mosyakin & Clemants - Tanzeel Zohra; Muhammad Ovais; Ali Talha Khalil; Muhammad Qasim; Muhammad Ayaz; Zabta Khan Shinwari (Natural Product Research, 2019)

Molecular docking and inhibition studies on the interactions of Bacopa monnieri’s potent phytochemicals against pathogenic Staphylococcus aureus - Talha Bin Emran; Md Atiar Rahman; Mir Muhammad Nasir Uddin; Raju Dash; Md Firoz Hossen; Mohammad Mohiuddin; Md Rashadul Alam (DARU Journal of Pharmaceutical Sciences, 2015)